Analysis of quantum algorithms - Farastu, Paresha; Sonnet, Rafiduzzaman; Hasan, Saddat; Paul, Sandipon (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.